Acid‐treated g‐C3N4‐Cu2O composite catalyst with enhanced photocatalytic activity under visible‐light irradiation. (20th June 2018) - Zuo, Shiyu; Xu, Haiming; Liao, Wei; Sun, Lei; Han, Donghui; Zan, Jie; Zhang, Binyang; Li, Dongya; Xia, Dongsheng
Abstract : Acid‐treated g‐C3 N4 ‐Cu2 O was prepared by hydrothermal reduction followed by high temperature calcination and acid exfoliation. The structures and properties of as‐synthesized samples were characterized using a range of techniques, such as X‐ray photoelectron spectroscopy, scanning electron microscopy, Photoluminescence Spectroscopy and the Brunauer–Emmett–Teller (BET) theory. The photocatalytic activity was evaluated by measuring the photodegradation of methyl orange under visible‐light irradiation. Based on the results of TEM, XPS, EPR and other techniques, it was verified that a heterojunction was formed. The acid treatment process can increase the specific surface area to form abundant heterojunction interfaces as channels for photo‐generated carrier separation, thereby enhancing its light utilization and quantum efficiency. Results indicate that acid‐treated g‐C3 N4 ‐Cu2 O possesses a large specific surface area, which provides plentiful activated sites for heterojunctions to form; in addition, it showed a high visible light effect and the minimum charge‐transfer resistance. Furthermore, the g‐C3 N4 ‐Cu2 O material exhibits high levels of effectiveness and stability. Electron paramagnetic resonance and a series of radical trapping experiments demonstrate that the holes and O2 − could be the main active species in methyl orange photodegradation. This work could provide new insights into the fabrication of composite materials as high‐performance photocatalysts, and facilitate their application in addressing environmental protection issues. Abstract : The g‐C3 N4 −Cu2 O was prepared by hydrothermal reduction followed by high temperature calcination and acid exfoliation. The acid treatment process can increase the specific surface area to form abundant heterojunction interfaces as channels for photo‐generated carrier separation, thereby enhancing its light utilization and quantum efficiency. This work could provide new insights into the fabrication of composite materials as high performance photocatalysts, and facilitate their application in addressing environmental protection issues.